Representation of Gender Relations in Mubadalah.Id Media: An Analysis of Sara Mills' Critical Discourse - Anis Safitri (International Journal of Scientific Multidisciplinary Research, 2025)
This research aims to critically analyze the discourses that represent gender relations in the media mubadalah.id. The research data are articles on mubadalah.id media with the titles “3 Stigma yang Terpatahkan dari Pernikahan Maudy Ayunda”, “Benarkah Laki-Laki Feminis Lebih Baik Daripada Perempuan Bukan Feminis?”, and “Tidak Wajar Jika Perempuan Tidak Bisa Memasak, Benarkah?”. The approach used in this study is a qualitative approach with a content analysis method. Data collection techniques with documentation, identification, and record techniques. The data analysis technique used is the perspective of critical discourse analysis from Sara Mills. The results showed the language construction in articles in mubadalah.id media represents equal gender relations. Based on the critical discourse analysis of Sara Mills' model, the subject-object and author-reader in the article mubadalah.id present women as empowered and equal figures with men. Thus, the data are taken from the media mubadalah.id represents a balanced and fair gender relationship. There is no inequality on one side. All use the perspective of relationship justice